Development of biotechnologically modified fat compositions enriched with omega-3 fatty acids using a two-stage transesterification method - Stankevych, Serhii; Kalyna, Viktoriia; Mezentseva, Iryna Oleksandrivna; Kolontaievskyi, Oleg; Ponomarova, Maryna; Belinska, Anna; Svishchova, Yana; Novikova, Viktoriia; Honcharenko, Yana (Technology center PC, 2025)
The object of the study is a two-stage combined transesterification of a fat composition to enrich the latter with ω-3 polyunsaturated fatty acids (PUFA). The problem was the need to create a stable fat system enriched with ω-3 PUFA, which is minimally oxidized during the production process. The rational parameters of the enzymatic stage of transesterification of fat substrates were substantiated (process temperature 65°C, fat substrate composition: refined deodorized soybean oil: intermediate fat system PMS-MF). The proposed conditions ensure the degree of transesterification of the fat composition at the level of 74.2% with the formation of 0.6% free fatty acids. The oxidative stability of the resulting product is maximum at 4°C, when in 30 days the peroxide value increases to 15.3 mmol ½O2/kg with losses of ω-3 PUFA of 5.1%. The results of the research are explained by the combination of two stages of transesterification: chemical modification of the fat matrix (product -PMS-MF) and enzymatic using Lipozyme TL IM, which minimizes hydrolytic and oxidative processes of labile components. The key distinguishing feature of the research is the combination of a high degree of enzymatic transesterification (74.2%) with a low level of by-products (0.6% free fatty acids). This was achieved due to the rational ratio of substrates and the temperature of enzymatic transesterification, at which ω-3 PUFA are introduced into the fat system. The obtained results open up prospects for the industrial production of health-promoting fat products with an increased content of ω-3 PUFA and specialized food systems. The technology is effective for fat raw materials with a content of ω-3 PUFA of 7±1% and a peroxide value of less than 1 mmol ½O2/kg.
Keywords: two-step transesterification; ω-3 polyunsaturated fatty acids; Lipozyme TL IM; oxidative stability; fat compositions